2009
DOI: 10.1128/jcm.00519-09
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of Human Immunodeficiency Virus Type 1 Load Caused by the Presence of Cells in Plasma from Plasma Preparation Tubes

Abstract: The human immunodeficiency virus type 1 (HIV-1) load is an important marker of disease progression and treatment efficacy in patients with HIV-1 infection. In recent years, an increase in the number of samples with detectable HIV-1 RNA has been reported among patients with previously suppressed viral loads, affecting clinical patient care and leading to repeat measurements of viral load and drug resistance. This rise seems to have coincided with the increased use of plasma preparation tubes (PPTs) for sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Artificially elevated HIV-1 RNA levels in PPTs are suggestive of HIV-1 viremia and consequently associated with clinical failure to HAART (1, 3, 4, 13). Recent reports have determined that elevated VLs in PPTs, linked to transient viremia or blips (14), are due to technical aberrations caused by cell-associated HIV nucleic acids (5,6,8). Our data clearly suggest that this artificial elevation in VL is due to the presence of HIV-1 proviral DNA from residual cells present in the plasma specimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificially elevated HIV-1 RNA levels in PPTs are suggestive of HIV-1 viremia and consequently associated with clinical failure to HAART (1, 3, 4, 13). Recent reports have determined that elevated VLs in PPTs, linked to transient viremia or blips (14), are due to technical aberrations caused by cell-associated HIV nucleic acids (5,6,8). Our data clearly suggest that this artificial elevation in VL is due to the presence of HIV-1 proviral DNA from residual cells present in the plasma specimen.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent prospective study, Kran et al (5) observed a direct correlation between the number of cells present in the plasma, measured in the Advia 60 cell counter, and the amount of HIV-1 that was quantified using the Roche COBAS AmpliPrep-COBAS TaqMan (CAP/TAQ) HIV-1 test. Using paired specimens that were collected and centrifuged in PPTs, they found lower cell counts and reduced HIV-1 VL in the PPTs that were recentrifuged prior to HIV-1 quantification versus the PPTs that were centrifuged once, after phlebotomy.…”
mentioning
confidence: 99%
“…Discrepancies in VL results obtained after freezing the plasma in situ in PPT are attributed to the presence and amplification of cellular proviral DNA in the extracted RNA that is used for testing (6), although some investigators believe that platelets associated with the virus could play a role in the process (9). In fact our own studies (13) identified the presence of integrated proviral DNA in the plasmas frozen in situ in PPT, suggesting that this proviral DNA, upon amplification in the Roche Cobas monitor assay, yielded quantifiable VL results.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recentrifugation of specimens transported in PPT at 4°C eliminated the inaccurate quantification of HIV seen in plasmas frozen in situ in PPT (6,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation